Comparative Effectiveness of Kinesio Taping and Ift in Upper Cross Syndrome- A Randomized Clinical Trial (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Upper cross syndrome refers to a particular configuration of overlapping overactive andunderactive muscle groups in the neck, chest and shoulders. Typically, poor posture causes the syndrome,including the forward head posture, which occurs when people use electronic devices, read, and drive. Thepresent study is intended to investigate the effect of kinesio taping on upper cross syndromeObjectives: 1. To study the effectiveness of kinesio taping, Hot Moist Pack and exercises in upper crosssyndrome, 2. To study the effectiveness of IFT, HMP and exercises in upper cross syndrome and 3. Tocompare the effectiveness of kinesio taping and IFT in upper cross syndrome.Methodology: The study consisted of 2 groups. Group A was experimental group and Group B wasconventional group. Both the groups received treatment protocol for 2 weeks. Sample size was 60 with 30in each group.Results: Visual analogue scale, cranio-vertebral angle and forward shoulder angle were used as outcomemeasures. Statistically significant results were found with VAS p=<0.0001, cranio-vertebral angle p=0.0632and forward shoulder angle p=0.285Conclusion: The study concluded that the use of kinesio taping is recommended in reducing pain andimproving the neck angles in participants with upper cross syndrome as compared to conventional therapy.